Allyl isothiocyanate attenuates oxidative stress and inflammation by modulating Nrf2/HO-1 and NF-?B pathways in traumatic brain injury in mice - Caglayan, Berrak; Kilic, Ertugrul; Dalay, Arman; Altunay, Serdar; Tuzcu, Mehmet; Erten, Fusun; Şahin, Kazım (Springer, 2019)
Traumatic brain injury (TBI) is the leading cause of mortality and morbidity in young adults and children in the industrialized countries; however, there are presently no FDA approved therapies. TBI results in oxidative stress due to the overproduction of reactive oxygen species and overwhelming of the endogenous antioxidant mechanisms. Recently, it has been reported that antioxidants including phytochemicals have a protective role against oxidative damage and inflammation after TBI. To analyze the effects of a naturally occurring antioxidant molecule, allyl isothiocyanate (AITC), on the nuclear factor erythroid 2-related factor 2 (Nrf2) and nuclear factor kappa B (NF-kappa B) signaling pathways in TBI, a cryogenic injury model was induced in mice. Here, we showed that AITC administered immediately after the injury significantly decreased infarct volume and blood-brain barrier (BBB) permeability. Protein levels of proinflammatory cytokines interleukin-1 beta (IL1 beta) and interleukin-6 (IL6), glial fibrillary acidic protein (GFAP) and NF-kappa B were decreased, while Nrf2, growth-associated protein 43 (GAP43) and neural cell adhesion molecule levels were increased with AITC when compared with vehicle control. Our results demonstrated that the antioxidant molecule AITC, when applied immediately after TBI, provided beneficial effects on inflammatory processes while improving infarct volume and BBB permeability. Increased levels of plasticity markers, as well as an antioxidant gene regulator, Nrf2, by AITC, suggest that future studies are warranted to assess the protective activities of dietary or medicinal AITC in clinical studies.
Keywords: Traumatic brain injury; Allyl isothiocyanate; NF-kappa B; Nrf2